A new species of Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Da Lat Plateau, Vietnam - Do, Quyen Hanh; Nguyen, Khoi Vu; Le, Minh Duc; Pham, Cuong The; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2021)
We describe a new species of the genus Hemiphyllodactylus on the basis of four specimens from Bidoup - Nui Ba National Park, Da Lat Plateau, Lam Dong Province, Vietnam. The new species, Hemiphyllodactylus dalatensis sp. nov., is distinguished from the remaining congeners by a combination of the following characters: a bisexual taxon; maximum SVL of 45.9 mm; dorsal scale rows 16; ventral scale rows 8 or 9; chin scales 7–10; postmental scales enlarged; femoral and precloacal pores in a continuous series, 23–25 in total in males, absent in the female; digital lamellae formula 4-5-5/6-5 (forefoot) and 5-6-6-6/5 (hind foot); cloacal spurs 2 or 3 on each side in both males and female; subcaudal scales not enlarged; dorsal trunk pattern with two paravertebral stripes, formed by two rows of dark spots; dark lateral head stripe distinct; postsacral mark cream or orange and bearing anteriorly projecting arms. In phylogenetic analyses, the new species is recovered as the sister taxon to a clade including all species from India although support values are low from all analyses.